THE IMPACT OF INSTITUTIONAL INVESTORS’ OWNERSHIP ON PERFORMANCE AND FINANCIAL POSITION: EVIDENCE FROM FIRMS IN THE REPUBLIC OF CROATIA (The South East European Journal of Economics and Business, 2021)
The research problem of this study is focused on examining the impact of the ownership of institutional investors on the corporate governance of Croatian companies. The problem was approached comprehensively such that institutional investors were analysed as both homogeneous and heterogeneous groups (investment funds, pension funds, insurance companies). The results of this study reveal a statistically significant impact of institutional investor ownership being viewed as both homogeneous and heterogeneous groups on business performance and financial position, which reduces the gap between ownership intentions and management interests, thereby resulting in an increase in shareholder wealth while limiting the satisfaction and social goals of a company.